Benzoyl transfer reactivities of racemic 2,4-Di-O-acyl-myo-inosityl 1,3,5-orthoesters in the solid state: molecular packing and intermolecular interactions correlate with the ease of the reaction - Sarmah, M. P.; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2005)
Racemic 2,4-di-O-acyl-myoinosityl 1,3,5-orthoesters undergo transesterification catalyzed by sodium carbonate with varying ease of reaction in the solid state; reactions in solution and melt do not show such varied differences. An interesting crystal of a 1:1 molecular complex of highly reactive racemic 2,4-di-O-benzoyl-myo-inosityl 1,3,5-orthoformate and its orthoacetate analogue exhibited better reactivity than the latter component alone. Single-crystal X-ray structures of the reactants have been correlated with the observed differences in the acyl-transfer efficiencies in the solid state. Although each of the derivatives helically self-assembles around the crystallographic 2(1) axis linked through O-(HO)-O-... hydrogen bonding, the pre-organization of the reactive groups (C=O [El] and OH [Nu]), C-(HO)-O-... and the C=H(...)pi interactions are significantly more favourable for the reactive derivatives than the less reactive ones. Bond-length distributions also showed differences; the O-C bond of the axial benzoyl group, which gets cleaved during the reaction, is longer (1.345-1.361 angstrom) relative to the chemically equivalent O-C bond of the equatorial benzoyl group (1.316-1.344 angstrom) in the reactive derivatives. These bond-length differences are not significant in the less reactive derivatives. The overall molecular organization is different too; the strikingly discrete helices, which may be viewed as ``reaction tunnels'' and are held by interhelical interactions, are clearly evident in the reactive derivatives in comparison with the less reactive ones.
Keywords: hydrogen bonds; Inositol; solid-state reactions; structure elucidation; transesterification

Biocatalyst mediated production of 6 beta,11 alpha-dihydroxy derivatives of 4-ene-3-one steroids - Kolet, Swati P.; Niloferjahan, Siddiqui; Haldar, Saikat; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (Steroids, 2013)
Biotransformation of steroids with 4-ene-3-one functionality such as progesterone (I), testosterone (II), 17 alpha-methyltestosterone (III), 4-androstene-3,17-dione (IV) and 19-nortestosterone (V) were studied by using a fungal system belonging to the genera of Mucor (M881). The fungal system efficiently and quantitatively converted these steroids in regio- and stereo-selective manner into corresponding 6 beta,11 alpha-dihydroxy compounds. Time course experiments suggested that the transformation was initiated by hydroxylation at 6 beta- or 11 alpha-(10 beta-hydroxy in case of V) to form monohydroxy derivatives which upon prolonged incubation were converted into corresponding 613,11oc-dihydroxy derivatives. The fermentation studies carried out using 5 L table-top fermentor with substrates (I and II) clearly indicates that 6 beta,11 alpha-dihydroxy derivatives of steroids with 4-ene-3-one functionality can be produced in large scale by using M881. (C) 2013 Elsevier Ltd.
Keywords: 4-Ene-3-one steroids; Biotransformation; Mucor sp.

Biocatalyst mediated functionalization of salannin, an insecticidal limonoid - Haldar, Saikat; Kolet, Swati P.; Dandekar, Devdutta S.; Kale, Balaji S.; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (RSC Advances, 2014)
Transformation of salannin, an insecticidal C-seco limonoid was investigated using a fungal system, Cunninghamella echinulata. Salannin was efficiently converted into two metabolites, where the C-17 furan moiety was transformed into gamma-hydroxybutenolide (salanninolide) and N-(2-hydroxyethyl)-alpha,beta-unsaturated-gamma-lactam (salanninactam) analogues. Present studies have indicated salanninolide to be a metabolite in the C-seco limonoid biosynthetic pathway.

Benz–amidinato stabilized a monomeric calcium Iodide and a lithium calciate(II) cluster featuring group 1 and group 2 elements - Yadav, Sandeep; Swamy, V. S. V. S. N.; Gonnade, Rajesh G.; Sen, Sakya S. (ChemistrySelect, 2016)
Soluble calcium halides reported so far are mostly dimeric in nature. The halides occupy the bridging position and thus provide additional coordination to the metal. We obtained a monomeric calcium iodide [{PhC(NiPr)(2)} CaI(thf)(3)] (1) from the reaction of [PhC(NiPr)(2)] Li with Cal(2) in THF. The compound has been stabilized by electronic donation and steric shielding from the amidinate ligand as well as coordination of three THF molecules. 1 does not show any propensity towards ligand exchange reaction. When the same reaction is carried out in diethyl ether instead of THF, it led to the formation of a Li calciate(II) cluster of composition L2Ca4I8Li4O (L= PhC(NiPr)(2)) (2) with an encapsulated O2+ in the middle of a tetrahedron spanned by four Ca2+ ions. 2 represents a metal-rich halide comprising of both alkali and alkaline earth metals which is quite unprecedented. Another notable aspect is that the amidinate ligand binds to the calcium atom in chelating bidentate mode in 1, whereas in 2 each N atom of the amidinate ligands binds to two Ca atoms leading to bridging bis-chelating coordination mode.

Base-free and catalyst-free synthesis of functionalized dihydrobenzoxazoles via vinylogous carbonate to carbamate rearrangement - Das, Tamal Kanti; Mondal, Santigopal; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2017)
An unexpected, catalyst-free, and base-free intramolecular cyclization of N-aryloxyacrylate aldimines, under thermal conditions leading to the synthesis of functionalized dihydrobenzoxazoles, is reported. The reaction features a unique rearrangement of vinylogous carbonates to vinylogous carbamates resulting in a new carbon–oxygen and carbon–nitrogen bond construction. The reaction tolerates a broad range of functional groups and the desired products are formed in moderate to good yields.

Biomimetic total synthesis of angiopterlactone B and other potential natural products - Kotammagari, Tharun K.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic Letters, 2017)
A one-pot biomimetic synthesis of (-)-angiopterlactone B and its enantiomer (+)-angiopterlactone B has been accomplished via TBAF-catalyzed tandem ring contraction followed by oxa-Michael/Michael addition sequence. Comparison of specific optical rotations, absolute configurations, and CD spectra of natural, synthesized (-)-angiopterlactone B and (+)-angiopterlactone B unequivocally proves that the isolated angiopterlactone B must be levorotatory. Synthesis of hitherto undiscovered natural products 18 and 20 and analogues of angiopterlactone B demonstrate the versatility of this method.